2021
DOI: 10.1177/09544089211050457
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of A-GTAW process using Box–Behnken design and hybrid BPNN-PSO approach

Abstract: Gas tungsten arc welding (GTAW) is the most extensively used process capable of fabricating a wide range of alloys based on its distinctive merits has been introduced. However, some demerits have been reported among which shallow penetration is the most crucial ones. In order to deal with the poor penetration of the process, different procedures have been proposed among which activated gas tungsten arc welding (A-GTAW) is the most extensively used one. In this study effect of percentage of activating fluxes (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 22 publications
(82 reference statements)
0
0
0
Order By: Relevance
“…The optimal I, V, and S reported were 140 A, 18 V, and 300 mm/min, respectively. The BW and DP models of the welded AISI316L were proposed in terms of the I and S, in which the PSO was used to find the best ANN model [6]. The small deviations (less than 4 %) indicated that the developed correlations were efficiently used in the GTAW operation.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal I, V, and S reported were 140 A, 18 V, and 300 mm/min, respectively. The BW and DP models of the welded AISI316L were proposed in terms of the I and S, in which the PSO was used to find the best ANN model [6]. The small deviations (less than 4 %) indicated that the developed correlations were efficiently used in the GTAW operation.…”
Section: Introductionmentioning
confidence: 99%